1993
DOI: 10.1002/1097-0142(19930201)71:3<735::aid-cncr2820710314>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Chordoma of the mobile spine. A clinicopathologic analysis of 40 patients

Abstract: Background. Chordomas are lobulated neoplasms composed of physaliphorous cells and their precursors; some have atypical, epithelioid, or spindle cell features. Fewer than one‐sixth of chordomas arise in the mobile (cervical, thoracic, or lumbar) spine. Forty‐eight percent originate in the sacrococcygeal region and 39% in the sphenoocciput. Methods. The study included 40 patients, 27 men and 13 women (2:1), with chordoma of the mobile spine. Their clinical and histopathologic features are described. Results. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
122
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(135 citation statements)
references
References 21 publications
9
122
0
3
Order By: Relevance
“…[16][17][18][19][20] Some authors, such as York et al, 7 have reported prolonged progression-free survival with radiotherapy for patients with subtotal resection, whereas others have reported that this had little effect. Because of the small sample that underwent adjuvant radiotherapy in the present study, our report is too limited to formulate any conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Some authors, such as York et al, 7 have reported prolonged progression-free survival with radiotherapy for patients with subtotal resection, whereas others have reported that this had little effect. Because of the small sample that underwent adjuvant radiotherapy in the present study, our report is too limited to formulate any conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Chordoma is thought to be a primary bone tumor that occurs with a predilection for the clivus and sacrum 1,3,6,9) . This anatomical distribution supports the generally accepted theory that it arises from notochordal remnants.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is gener-ally agreed that complete surgical excision of the tumor is the only curative procedure 8) . As has been recognized so far, recurrence rates after any treatments of chordomas have been high and unsatisfactory 1,3,4) . Surgical resection has become more aggressive in recent years evolving from intralesional debulking to total resection to reduce local recurrence rate 4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of notocordal origin and arises along the cranio-coccygeal axis. Chordoma accounts for approximately 5% of all malignant bony neoplasms [1]. About 50% arise from the sacrococcygeal region, 35% from the spheno-occipital region and 15% along the spinal axis [2].…”
Section: Introductionmentioning
confidence: 99%